Vibration excitation identification and control of the cutter of a combine harvester using triaxial accelerometers and partial coherence sorting. (September 2019) - Pang, Jing; Li, Yaoming; Ji, Jiangtao; Xu, Lizhang
Abstract : To control the key structures vibration of combine harvesters, e.g. the driver's seat, the partial coherence mode of the cutter driving system has been set up based on the structural model. The vibration of the cutter is transmitted to the cutting platform through three connection positions - the cutter chute, the rocker shaft seat and the middle shaft seat of the header. For the three junction points from the cutter system to the cutting platform, the time-domain and frequency-domain characteristics of the vibration response are measured and analysed. The main exciting source sequence of Y direction vibration on seat fixing point is considered as the Y direction of cutter chute, Y direction of rocker shaft, Y direction of the middle shaft of the header, and Z direction of cutter chute. Moreover, the correctness of the order above is verified using partial-coherence method. Considering that the cutter chute is the main source, a nut with a rubber sleeve is designed to reduce the vibration transformed from cutter bar to chute. The experiment has verified that this method is able to reduce the Y direction vibration intensity of the seat fixing points by 10.78%. Highlights: Determine vibration transmitted to the platform through 3 connecting positions. Partial-coherence method used to order the methods of vibration transmission. Nut with rubber sleeve used to reduce vibration transmission from cutter bar to chute.